Expression, Characterisation and Structural Homology Modelling of Recombinant Mercuric Reductase of Streptomyces sp. AS2 - Khasanah, Anis Uswatun; Putri, Wahyu Aristyaning; Rahayu, Hanum Mukti; Sembiring, Langkah; Purwestri, Yekti Asih (Universitas Gadjah Mada, 2024)
Mercury pollution poses a significant environmental challenge worldwide, prompting extensive efforts over the past two decades to combat its detrimental effects. Cloning merA from Streptomyces sp. AS2 (Accession numbers LC026157) into the expression vector pET-28c (+) marks a critical advancement in this field, necessitating further investigation into the expression and structural analysis of the resulting recombinant mercuric reductase protein. This study aimed to optimise the expression and characterise the structural MerA protein. The study involved the expression of merA from AS2 isolate in the host Escherichia coli BL21 and the measurement of mercuric reductase using SDS-PAGE. Induction of E. coli BL21 was optimized by adding IPTG concentration and incubation time. Purification of mercuric reductase was attempted using ammonium sulphate precipitation, dialysis, and column chromatography. Protein structural characterisation was conducted using computational modelling tools Swiss-Model and Phyre2. Expression of merA from AS2 isolate was successfully performed in E. coli BL21, with SDS-PAGE showing a dominant band in the 55-70 kDa range using IPTG concentration 1 and 1,2 mM and 18-hour incubation time. The specific activity of mercuric reductase was obtained at an enzyme concentration of 294.07 Unit/mg. Protein structural characterisation revealed homology with Lysinibacillus sphaericus (Swiss-Model) and similar folding to c5c1Yc, a known mercuric reductase from the same species using Phyre2. The successful expression of recombinant pET-28c (+)-MerA in E. coli BL21 offers new opportunities for bioremediation efforts targeting mercury contamination.